A point prevalence survey to assess antibiotic prescribing in patients hospitalized with confirmed and suspected coronavirus disease 2019 (COVID-19). (March 2021) - Tan, Sock Hoon; Ng, Tat Ming; Tay, Hui Lin; Yap, Min Yi; Heng, Shi Thong; Loo, Audrey Yong Xin; Teng, Christine B.; Lee, Tau Hong
Abstract: Background: Earlier studies have reported high antibiotic use in patients hospitalised for coronavirus disease 2019 (COVID-19), resulting in concerns of increasing antimicrobial resistance with increase antibiotic use in this pandemic. Point prevalence survey (PPS) can be a quick tool to provide antibiotic prescribing information to aid antimicrobial stewardship (AMS) activities. Objectives: To describe antibiotic utilization and evaluate antibiotic appropriateness in COVID-19 patients using PPS. Methods: Adapting Global-PPS on antimicrobial use, the survey was conducted in COVID-19 wards at 2 centres in Singapore on 22 April 2020 at 0800h. Patients on systemic antibiotics were included and evaluated for antibiotic appropriateness. Results: Five hundred and seventy-seven patients were screened. Thirty-six (6.2%) patients were on antibiotics and which were started at median of 7 days (inter-quartile rate (IQR), 4, 11) from symptom onset. Fifty-one antibiotics were prescribed in these patients. Overall, co-amoxiclav (26/51, 51.0%) was the most often prescribed antibiotic. Thirty-one out of 51 (60.8%) antibiotic prescriptions were appropriate. Among 20 inappropriate prescriptions, 18 (90.0%) were initiated in patients with low likelihood of bacterial infections. Antibiotic prescriptions were more appropriate when reviewed by infectious diseases physicians (13/31 [41.9%] versus 2/20 [10.0%], p = 0.015), and if reasons for use were stated in notes (31/31 [100.0%] versus 16/20 [80.0%], p = 0.019). Conclusions: Despite low prevalence of antibiotic use among confirmed and suspected COVID-19 patients at 2 centres in Singapore, there was significant proportion of inappropriate antibiotics use where bacterial infections were unlikely. AMS teams can tailor stewardship strategies using PPS results.